Designing a Blended Learning Course on Pedagogy of Science of Pre-service Teacher Education Programme - Krishnan, Dhanya (JOURNAL OF INDIAN EDUCATION, 2022)
Blended learning, an innovative pedagogical approach, has been emerged as a catalyst in optimising learning by strengthening the prospects of online and face-to-face mode of learning. This has a lot of relevance in teacher preparation programmes with its potential for providing multiple learning opportunities. Student teachers are in the process of becoming ‘reflective practitioners’ and so blending the strengths of online learning along with face-to-face instruction could be of immense help. It provides room for open communication and deeper analysis on wider platforms by allowing flexibility, convenience and critical reflection that online mode offers along with the benefits of in-person communication and interaction inside the classroom. However, designing a highly participatory, reflective blended learning course on Pedagogy of Science is challenging. This paper is an attempt to reflect on the relevance and scope of blended learning course on the pedagogy of science in a teacher education programme. Theoretical perspectives of blended learning are analysed in detail. The paper also provides an exemplar model of blended course that may be adapted or explored further while redesigning the course on Pedagogy of Science as a blended course in teacher education programme.